Dense genotyping of immune-related susceptibility loci reveals new insights into the genetics of psoriatic arthritis - Mc Manus, Ross; Kane, David (My University, 2015)
Poriatic arthritis (PsA) is a chronic inflammatory arthritis associated with psoriasis and, despite the larger estimated heritability for PsA, the majority of genetic susceptibility loci identified to date are shared with psoriasis. Here, we present results from a case–control association study on 1,962 PsA patients and 8,923 controls using the Immunochip genotyping array. We identify eight loci passing genome-wide significance, secondary independent effects at three loci and a distinct PsA-specific variant at the IL23R locus. We report two novel loci and evidence of a novel PsA-specific association at chromosome 5q31. Imputation of classical HLA alleles, amino acids and SNPs across the MHC region highlights three independent associations to class I genes. Finally, we find an enrichment of associated variants to markers of open chromatin in CD8 þ memory primary Tcells. This study identifies key insights into the genetics of PsA that could begin to explain fundamental differences between psoriasis and PsA.
PUBLISHED
Keywords: psoriatic arthritis (PsA); psoriatic arthritis (PsA); Genes & Society; Immunology, Inflammation & Infection